Manajemen Pendidikan Karakter Santri dalam Menjawab Tantangan Modernitas Zaman di Era Globalisasi - Samino Samino; Fitri Nur Mahmudah (Jurnal Syntax Admiration, 2023)
Islamic boarding schools in their development are required to make changes in line with the demands of the world with the advancement of science in life. Islamic boarding schools consciously adapt to globalization as a dynamic that cannot be avoided, this global current causes changes in all aspects of life, including in the world of education, and Islamic boarding schools also participate in the assimilation of science and modern technology. The Islamic boarding school education system has shifted towards a more positive direction, structurally and culturally concerning leadership patterns, leadership and santri relationship patterns, communication patterns, and decision-making methods. Islamic boarding schools respond to changes that occur by revitalizing teaching patterns so that they are able to grow scientific traditions and give birth to generations of learning, revitalizing pesantren leadership patterns so that they are more open to all changes, and revitalizing a more conducive, comprehensive and empowering learning environment.